2014
DOI: 10.1093/rfs/hhu040
|View full text |Cite
|
Sign up to set email alerts
|

Fooling Some of the People All of the Time: The Inefficient Performance and Persistence of Commodity Trading Advisors

Abstract: , and seminar participants at UMass Amherst. The views expressed are those of the authors and do not necessarily reflect the official position of AIG Financial Products Corp or the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 59 publications
4
24
0
Order By: Relevance
“…It focuses on speculative factors, here defined as the trade-off between interest rates on 3 I am indebted to Larry Summers for this point. 4 For example, World Economic Outlook, International Monetary Fund, October 2007, April 2008and October 2008. Also OECD and World Bank.…”
Section: Macroeconomic Influencesmentioning
confidence: 99%
“…It focuses on speculative factors, here defined as the trade-off between interest rates on 3 I am indebted to Larry Summers for this point. 4 For example, World Economic Outlook, International Monetary Fund, October 2007, April 2008and October 2008. Also OECD and World Bank.…”
Section: Macroeconomic Influencesmentioning
confidence: 99%
“…In doing so, we add to the literature on the performance of CTAs, which is generally positive (e.g., Schneeweis, Savanayana, and McCarthy [1991]; Schneeweis, Spurgin, and McCarthy [1997]; Edwards [1998]; Liang [2004]; Gregoriou et al [2005]; Kazemi and Li [2009]; Gregoriou, Hübner, and Kooli [2010]; Arnold [2012];and Schneeweis, Spurgin, and Szado [2012]), with the exception of two early studies (Elton, Gruber, andRentzler [1987, 1990]) and a recent article (Bhardwaj, Gorton, and Rouwenhorst [2014]). A related literature also highlights the diversification benefits of CTAs as part of a broader institutional portfolio (e.g., Fung andHsieh [2000, 2001], Edwards and Caglayan [2001], and Mulvey [2012]), emphasizing the strong performance in equity and bond bear markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent academic attention has focused on how to address this bias without introducing further bias to the study. For example, Bhardwaj, Gorton, and Rouwenhorst [2014] and Getmansky, Lee, and Lo [2015] removed any observations prior to the "date added" field in the TASS database. However, subsequent evidence by Jorion and Schwarz [2014] indicated that this approach is likely to overstate backfill bias because many funds in TASS in fact report to Hedge Fund Research (HFR) at an earlier date.…”
Section: Cta Returns Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Should the investment drop in value, then the managers must bring it back above the previous highest value before they become eligible for performance fees again. Bhardwaj et al (2008) CTAs for perceived diversification benefits and mandates for alternative investments (e.g., pension funds) and end up staying invested despite facing poor performance.…”
Section: Recent Studies In the 2000smentioning
confidence: 99%